Brit awards announce voting shakeup after #BritsSoWhite outrage (the Guardian, 2016)
Organisers say academy is more gender-balanced and diverse after last year’s failure to nominate black artists
Section: Music

How to be a boss woman in the music industry - Jones, Rhian (Medium, 2016)
The music industry is hugely homogenised. In the UK, all three heads of the major record labels are men, and there’s just three women…

Drugs at the campsite: Socio-spatial relations and drug use at music festivals - Dilkes-Frayne, Ella (International Journal of Drug Policy, 2016)
Background Music festivals have received relatively little research attention despite being key sites for alcohol and drug use among young people internationally. Research into music festivals and the social contexts of drug use more generally, has tended to focus on social and cultural processes without sufficient regard for the mediating role of space and spatial processes. Methods Adopting a relational approach to space and the social, from Actor-Network Theory and human geography, I examine how socio-spatial relations are generated in campsites at multiple-day music festivals. The data are drawn from ethnographic observations at music festivals around Melbourne, Australia; interviews with 18–23 year olds; and participant-written diaries. Results Through the analysis, the campsite is revealed as a space in process, the making of which is bound up in how drug use unfolds. Campsite relations mediate the formation of drug knowledge and norms, informal harm reduction practices, access to and exchange of drugs, and rest and recovery following drug use. Conclusions Greater attendance to socio-spatial relations affords new insights regarding how festival spaces and their social effects are generated, and how they give rise to particular drug use practices. These findings also point to how festival harm reduction strategies might be enhanced through the promotion of enabling socio-spatial relations.
Keywords: Drug use; Enabling places; Ethnography; Music festivals; Social context; Socio-spatial relations

Nightlife Ethnography, Violence, Policing and Security - Tomsen, Stephen; Wadds, Phillip (2016)

Post-postfeminism? New feminist visibilities in postfeminist times - Gill, R. (Feminist Media Studies, 2016)
This article contributes to debates about the value and utility of the notion of postfeminism for a seemingly “new” moment marked by a resurgence of interest in feminism in the media and among young women. The paper reviews current understandings of postfeminism and criticisms of the term’s failure to speak to or connect with contemporary feminism. It offers a defence of the continued importance of a critical notion of postfeminism, used as an analytical category to capture a distinctive contradictory-but-patterned sensibility intimately connected to neoliberalism. The paper raises questions about the meaning of the apparent new visibility of feminism and highlights the multiplicity of different feminisms currently circulating in mainstream media culture – which exist in tension with each other. I argue for the importance of being able to “think together” the rise of popular feminism alongside and in tandem with intensified misogyny. I further show how a postfeminist sensibility informs even those media productions that ostensibly celebrate the new feminism. Ultimately, the paper argues that claims that we have moved “beyond” postfeminism are (sadly) premature, and the notion still has much to offer feminist cultural critics.
Number: 4

Cultural value and cultural policy: some evidence from the world of live music - Behr, Adam; Brennan, Matt; Cloonan, Martin (International Journal of Cultural Policy, 2016)
This article considers live music policy in relation to wider debates on the cultural (as opposed to instrumental) value of the arts. The findings are based on research into amateur/enthusiast, state-funded and commercial concerts across a range of genres – classical, traditional folk, jazz, singer–songwriter and indie – using the Edinburgh Queen’s Hall venue as a case study. We argue that (1) articulations of the cultural or intrinsic value of live music across genres tend to lapse back into descriptions of instrumental value; (2) although explanations vary from audiences, artists and promoters as to why they participate in live music, they also share certain characteristics across genres and sometimes challenge stereotypes about genre-specific behaviours; and (3) there are lessons to be learned for live music policy from examining a venue that plays host to a range of genres and promotional practices.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2014.987668
Keywords: audience research; cultural value; live music; music policy; regulation

How can the music industry tackle its diversity issues? (Music Business Worldwide, 2016)
Kieron Faller from CI reveals best-practice for diverse businesses…

Taking time between g-string changes to educate ourselves: Sinéad O’Connor, Miley Cyrus, and celebrity feminism - Brady, Anita (Feminist Media Studies, 2016)
This article examines the feminist response to a 2013 online “feud” between singers Miley Cyrus and Sinéad O’Connor that began when Cyrus connected the video for her single “Wrecking Ball” to O’Connor’s video for “Nothing Compares 2 U.” O’Connor’s response criticised Cyrus’ sexualised image, and the exchanges that followed sparked debate among feminists over the limits of sexual “agency,” and the sexual politics of feminism. This took place within a wider media context that has seen an apparent increase in female celebrities explicitly identifying themselves as feminist. Critics of this “celebrity feminism” argue that the sexualised star systems of its proponents are at odds with the aims of feminist politics. This article draws on post-structuralist feminist theory to question the positioning of celebrity feminism as exterior to an imagined “feminist movement.” Using the Cyrus/O’Connor feud, I argue that such a binary potentially reaffirms the structures of power that feminism seeks to oppose, and ignores the ways celebrity culture and contemporary media practice might combine to produce new understandings of the field of feminism.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2015.1137960
Keywords: Celebrity feminism; Miley Cyrus; Sinéad O’Connor; feminist post-structuralism; third-wave feminism

Risky Pleasures?: Club Cultures and Feminine Identities - Hutton, Fiona (Routledge, 2016)
In this book Fiona Hutton provides a fascinating insight into women's experiences of clubbing. Based on a rich ethnographic account of the Manchester club scene, Risky Pleasures? is set within the context of the theoretical literature on youth subcultures, female friendship, consumption, risk and the city. The work highlights both the producers of club scenes - promoters, DJs, dealers - and the consumers - women negotiating pleasure and risk in club spaces and in the city at night. It explores the range of club spaces, developing a typology of 'mainstream' and 'underground' clubs, and considers how different types of participants are attracted to different 'scenes'. It examines women's recreational drug-use within a club context and discusses issues of sexuality, tolerance and the importance of 'attitude' in terms of women's feelings of safety. Revealing the important role of different spaces and different atmospheres in how women participate in club scenes, Fiona Hutton argues that drug taking and sexual pleasure are always contextualized within the environments created in different spaces, and that the risk and danger negotiated by women clubbers are counterbalanced by fun and pleasure - and ultimately empowerment.

Challenging the Myth of Gender Equality in Sweden - Lena, Martinsson; Gabriele, Griffin (Policy Press, 2016)
Sweden is often considered one of the most gender-equal countries in the world and held up as a model to follow, but the reality is more complex. This is the first book to explode the myth of Swedish gender equality, both offering a new perspective for an international audience, and suggesting how equality might be rethought more generally. While the authors argue that the gender-equality mantra in Sweden has led to a society with increased opportunities for some, they also assert that the dominant norm of gender equality has become nationalistic and builds upon heteronormative and racial principles. Examining the changing meanings and parameters of gender equality against the country's social-democratic tradition and in the light of contemporary neoliberal ideologies, the book constitutes an urgent contribution to the debates about gender-equality policies and politics.
Keywords: Social Science / Gender Studies; Social Science / Sociology / General

Valuing Musical Participation - Pitts, Stephanie (Routledge, 2016)
Increasingly, it is becoming evident that those involved in socio-musical studies must focus their investigative lens on musical practice and articulation of the self, on music and community involvement and on music as a social medium for social relationships. What motivates people to be involved in musical performance, and how do they articulate these needs and drives? What do performers gain from their involvement in musical activities? How do audience members perceive their relationship to the performer, the music and the event? These questions and many more are addressed here with the benefit of detailed empirical work, including case studies of a chamber music festival and a contemporary music summer school. Pitts investigates the value of musical participation for performers and audience members in a range of contexts, using a multi-disciplinary approach to place new empirical data in the framework of existing theory and literature. Themes examined include: the shared musical experience; the social structures of performing societies; how people identify with music; the values implicit in musical preferences; the social responsibilities of the performer; the audience view of concerts and festivals; the social power of music and educational implications and responsibilities. Pitts draws upon literature from musicology, sociology and psychology of music, ethnomusicology, music education and community music to demonstrate the diversity of enquiry about musical behaviours. The conclusions of the book are based upon empirical evidence gleaned through case studies, with the data integrated thematically throughout, to enable a greater depth of discussion than individual studies usually permit.

Who are the most powerful people in music? Jay Z? Kanye? Beyoncé? No, it’s old white men (the Guardian, 2016)
The 2016 Billboard Power 100 is dominated by white men born before Elvis had a hit. This isn’t only a problem of representation – it’s also bad for the industry
Section: Music

Learning to labour unequally: Understanding the relationship between cultural production, cultural consumption and inequality - Oakley, Kate; O'Brien, Dave (Social Identities, 2016)
Inequality has become essential to understanding contemporary society and is at the forefront of media, political and practice discussions of the future of the arts, particularly in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The article considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The paper argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy, despite the importance of culture to British and thus international policy agendas. The article uses the example of higher education in the UK to think through the relationship between cultural consumption and production. In doing, so the article maps out a productive possibility for a new research agenda, by sketching where and how research might link cultural consumption and production to better understand inequality.

Gender, Metal and the Media: An Introduction - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill offers a much needed discussion of the lack of consideration given to gender in academic discussions of hard rock and metal music and the media. Drawing on her own experience as a musician and fan, the author argues that orthodoxies—e.g., the genre is inclusive, the music asexual and sexism non-existent—are only able to persist within the literature because scholars have neglected to understand how musical experiences are gendered. Within the context of feminist popular music scholarship, work on fandom and feminist methodological work, Hill outlines the need to study hard rock, metal and the media with close attention to the influence of gender.
Keywords: Black Metal; Hard Rock; Metal Music; Rock Music; Social Expression

Hard Rock and Metal as an Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill examines the differing theoretical frameworks, e.g., subculture and scene, used to examine hard rock and metal fans, arguing that these have worked to the detriment of understanding the gendered experience of music, including taking pleasure in the music. She proposes a new way of thinking about fandom that incorporates fans’ feelings of community. Drawing on Anderson’s (Imagined Communities: Reflections on the Origin and Spread of Nationalism. Verso, 1991) theory of the nation, and feminist writings on community (Weiss and Friedman, Feminism and Community. Temple University Press, 1995), she argues that ‘imaginary community’ better reflects fans’ sense of community, whilst allowing deep consideration of the ideology of the community with particular reference to values, beliefs, traditions and myths. She argues that these are deployed to create a sense of cohesion in spite of inequalities and unacknowledged privileges.
Keywords: Extreme Metal; Gender Construction; Hard Rock; Metal Community; Moral Panic

Listening to Hard Rock and Metal Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter challenges readings of hard rock and metal as masculine music. Hill examines women’s accounts of their experiences of musical pleasure. Through analysis of women fans’ descriptions of their favourite bands, she argues that, pace Kahn-Harris (2007), fans can be very articulate about what they like. Work of feminist writers on rock music is enlisted to argue that considering women’s listening pleasure gives new insights into the meaning of hard rock and metal music. The assumption that hard rock and metal is a masculine genre neglects important aspects of women’s fandom which diverge from the dominant myths.
Keywords: False Consciousness; Hard Rock; Heavy Metal; Musical Experience; Rock Music

Metal and Sexism - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 6 considers the allegations that hard rock and metal is sexist. Talking to British women fans reveals that in their experiences, hard rock and metal is less sexist than the ‘mainstream’. Using research on sexism across a range of fields, Hill argues that understanding what counts as sexism is complex and requires critical work by fans when sexism is normalised. Listening to what fans say about the context of their experiences within their broader lives is vital for better understanding. The author argues that the genre provides moments in which women fans may gain a feeling of genderlessness. Ultimately, however, the feeling of liberation only comes through assimilation into the culture, a culture that ignores women as much as possible. Nevertheless, that temporary feeling is a valuable one.
Keywords: Hard Rock; Metal Event; Music Video; Sexual Harassment; Unwanted Sexual Attention

The Gendered Experience of Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
The final chapter argues that close examination of the specific experiences of women in their engagements with the hard rock and metal media, the music, and musical events reveals how the experience of music is shaped by sexist assumptions about women and about how music should be listened to. Musical pleasure does not exist on a universal, transcendental plane. It is informed and shaped by the socio-cultural circumstances of the listener. Hill maintains that it is vital to acknowledge how these circumstances make for differing experiences: it is an important first step for countering sexism. The chapter concludes with a short plan for how hard rock and metal may imagine a genderless future, and how this imagined community might work towards it.
Keywords: Hard Rock; Metal Musician; Music Culture; Normative Femininity; Science Fiction

The Media and the Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter investigates how Kerrang! magazine, a key part of the metal media, creates an imaginary community of hard rock and metal fans. Using semiotic analysis, the author extrapolates four myths that are forged in the letters pages: two that are presented by the magazine as being common sense values of the community (equality and authenticity) and two that are less obvious, the groupie and the warrior, which determine how women and men are portrayed. These myths work together to depict the imaginary community as ideologically invested in maintaining the masculinity of the genre at the expense of femininity. Hill argues that dominant representations of women in the imaginary community render them as adjuncts to the real members of the community—the men—and this has damaging consequences.
Keywords: Hard Rock; Hegemonic Masculinity; Horror Film; Letter Writer; Metal Community

Women Fans and the Myth of the Groupie - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 4 scrutinises the impact that the myth that women fans are groupies has on British hard rock and metal women fans. Women fans must negotiate the stereotype without accepting the title if they want their fandom to be respected, this results in a defensiveness about sexual and fannish reputations, which is an overtly gendered experience. Hill moves to examine the ways in which women’s desire for musicians and the complicated ways in which it must be negotiated impact on fans’ ability to express their fandom and their sexuality. The problem of the groupie myth lies not just with the expectations it places upon women but also in the ways in which it prevents discussion of more sensual and embodied experiences of musical pleasure.
Keywords: Hard Rock; Music Industry; Physical Attraction; Sexual Attraction; Sexual Pleasure